2004
DOI: 10.1086/421698
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Properties of Helium‐rich, Degenerate Dwarfs in Binaries Containing Compact Companions

Abstract: The evolution of binaries containing low-mass donors ( 2 M ) and degenerate accretors (i.e., white dwarfs [0.7 M ] or neutron stars [1.4 M ]) is systematically investigated over a wide expanse of parameter space. The donors are assumed to have metallicities in the range of 0:0001 Z 0:02 and could be either unevolved (zeroage main sequence) or ascending the red giant branch at the onset of mass transfer [corresponding to 5 P P orb (hr) P 2 ; 10 3 ]. The evolutionary tracks form part of a very detailed grid of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
110
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(125 citation statements)
references
References 77 publications
11
110
0
Order By: Relevance
“…It should be mentioned that in this paper we have not considered different values of the initial mass of the secondary (mass-losing) star. Although the envelope mass of the resulting white dwarf, a key factor in dictating the cooling times, is expected to be only weakly dependent on the initial mass of the mass-losing star (Nelson et al 2004), different orbital angular-momentum loss prescriptions due to mass loss could have an impact on the final envelope mass. This issue has not been considered in this paper.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be mentioned that in this paper we have not considered different values of the initial mass of the secondary (mass-losing) star. Although the envelope mass of the resulting white dwarf, a key factor in dictating the cooling times, is expected to be only weakly dependent on the initial mass of the mass-losing star (Nelson et al 2004), different orbital angular-momentum loss prescriptions due to mass loss could have an impact on the final envelope mass. This issue has not been considered in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 14 initial He-core white dwarf models with stellar masses between 0.155 and 0.435 M were derived for initial orbital periods at the beginning of the Roche lobe phase in the range 0.9 to 300 d. In particular, nine sequences span the range of masses corresponding to ELM white dwarfs (M 0.20 M ). At this point, it is worth mentioning that the envelope mass of the resulting white dwarf, a key factor in dictating the cooling times, is only weakly dependent on the initial mass of the secondary (mass-losing) star (Nelson et al 2004). However, different angular-momentum loss prescriptions due to mass loss, which could have an impact on the final envelope mass, have not been explored in this paper.…”
Section: Numerical Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting ages are thus much greater than those resulting from considering only the decrease in the thermal content of the ions. More recently, Nelson et al (2004) have also found that hydrogen burning strongly delays the cooling process, especially for very low-mass white dwarfs. They found flashes taking place for masses in the range 0.21 M < ∼ M WD < ∼ 0.28 M , in good agreement with the predictions of Driebe et al (1998).…”
Section: Evolutionary Calculations For He-core White Dwarfsmentioning
confidence: 99%
“…The constraints placed on their total ages help retrace the prior evolution of these systems (see Tauris & Savonije 1999;Nelemans et al 2001;Nelson et al 2004).…”
Section: Introductionmentioning
confidence: 99%